The Association of Different Sedentary Patterns and Health-Related Physical Fitness in Pre-schoolers - Lu, Yanhua; Li, Yiyan; Zhou, Tang; Sang, Menghao; Li, Longkai; Fang, Chunyi; Hu, Wenwen; Quan, Minghui (Frontiers in Pediatrics, 2022)
Background: The results of sedentary time (ST) and Health-related physical fitness (HPF) are not completely consistent, and the studies concentrated preschoolers are very limited. Methods: We measured ST and ST patterns (ST Bouts time, ST Breaks times) by accelerometer. The Health-related physical fitness T-score (HPFT) was calculated by five indexes: height-weight standard score, 20m shuttle-run test, grip-strength, standing long jump and 2×10m shuttle-run test. Results: We included 375 preschoolers (211 boys, 164 girls) in the final analysis. The total ST and ST Bouts time negatively correlated with HPFT in preschoolers. HPFT reduced by 1.69 and 0.70 points for per 10 min increased in total ST and ST Bouts time respectively. HPFT of highest quartile group reduced by 9.85 points in total ST, and 10.54 points in ST Bouts time compared with the lowest quartile group. However, the HPFT increased by 0.09 points for per 10 times increased in ST Breaks times; the HPFT increased by 16.21 and 15.59 points when moderate to vigorous physical activity (MVPA) replaced total ST and ST Bouts time. Conclusions: HPF negatively correlated with the Total ST and ST Bouts time, but positively correlated with ST Breaks times; and HPF significantly improved when MVPA replaced ST in preschoolers.